Perancangan User Experience Aplikasi Mobile Platform BagiKata menggunakan Metode Goal-Directed Design (GDD) - Rizka Ghaniyyah; Buce Trias Hanggara; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Bagikata is a question and answer platform that can connect users with various contributors or counselors who are experienced in the mental health field. In its use, users still experience several problems, including the limited platform owned by the user and the absence of a unified system to provide all the services needed by the user. While Bagikata wants an interface design that can meet the needs of its users, Bagikata has never researched what is needed and what are the problems of its users. This study aims to produce a design for the BagiKata mobile application using 5 phases in the Goal-Directed Design method. In the research phase, needs analysis from stakeholders and users is obtained. In the modeling phase, one persona is generated from a group of users and a user journey. In the requirements phase, scenario context, requirements, and information architecture are generated. In the framework phase, a system design and a mobile application design framework are generated. In the refinement phase, a high-fidelity prototype is produced and tested using the User Testing and User Experience Questionnaire. Testing with the User Experience Questionnaire resulted in a mean value with a positive category on each UEQ scale. In the UEQ Benchmark, the Attractiveness, Efficiency, Accuracy, and Stimulation scales are classified into the Excellent (Very Good) category on the Benchmark. Meanwhile, the Clarity and Novelty scale belongs to the Good category on the Benchmark.